O Instituto Histórico e Geográfico Brasileiro (IHGB) e o primeiro governo de Getúlio Vargas (1930-1945) - Trevisan, Ivan Rodrigo (2021)
In this doctoral dissertation, we analyze the relations between the Brazilian Historical and Geographical Institute (IHGB) and the first Getúlio Vargas Regime (1930-1945). Our study is based on four factors: (1) the institutional relationship between IHGB and the head of Brazil, which evinces that there was a networking group in which members of both the Institute and the government participated; (2) IHGB’s political views on both government actions and the main events/political debates in Brazil at that time; (3) the government funding of IHGB; and finally, (4) the activities and projects IHGB developed along with Vargas’ administration which were dedicated to the field of History—especially conducted within the Ministry of Education, where IHGB was considered to be a vector of Vargas’ cultural policy.